A Pengaruh Jumlah Uang Beredar dan Pertumbuhan Ekonomi Terhadap Inflasi - Fenty Y Manuhuttu (Musamus Journal of Economics Development, 2023)
This study aims to determine the effect of the money supply and economic growth on inflation in Indonesia. This research is limited by analyzing annual quantitative secondary data in the time range between 2010-2022. The data is processed again according to the needs of the model used. Data sources come from statistics published by the Central Bureau of Statistics and Bank Indonesia. Data were processed using SPSS version 25. The results showed that the money supply variable partially had a negative and significant effect on inflation, with a coefficient value of -0.725 and a significance value of 0.046. The economic growth variable partially has a negative and insignificant impact on inflation, with a coefficient value of -0.433 and a significance value of 0.523. Simultaneously the money supply and economic growth have no effect on inflation in Indonesia for the 2010-2022 period.